The Criticism on the Meaning of âOpen Legal Policyâ in Verdicts of Judicial Review at the Constitutional Court Mardian Wibowo - Wibowo, Mardian; Nurjaya, I Nyoman; Safaat, Muchammad Ali (The Constitutional Court of the Republic of Indonesia, 2017)
In several verdicts of judicial review, the Constitutional Court formulates a concept of Open Legal Policy. The concept begins from a condition when a norm of law submitted to judicial review by the 1945 Constitution does not have reference in the 1945 Constitution. In other words, the open legal policy is a condition when the Constitutional Court cannot find any reference for the norm submitted to the judicial review. By using a construction method, this present research tries to find the meaning of a concept of open legal policy arranged by the Constitutional Court, then assessing whether the concept is in line with the spirit of judicial review. If the formulation of the concept done by the Constitutional Court has not been ideal, the deconstruction will be conducted toward the meaning that already exists until the open legal policy ideal with the perspective of the constitution is found. In this research, the finding shows different meaning of open legal policy between various verdicts of the Constitutional Court. Moreover, a new meaning is proposed including improvement of criteria of the open legal policy based on the difference between the object of regulation (what) and the content of the regulation (how).